Radical resection of large metastatic non-functioning pancreatic neuroendocrine carcinoma complicated by splenic vein thrombosis and sinistral portal hypertension. (April 2021) - Kumar, S.; Raobiakady, R.; Watkins, D.; Terlizzo, M.; Bhogal, R.H.
Highlights: Pancreatic Neuroendocrine Carcinoma (PNECs) are rare tumours with only a few reports of successful surgical resection. PNECs can cause splenic vein thrombosis and resulting sinistral hypertension that can increase the complexity of surgical resection. Multi-visceral resections for metastatic PNECs have not been previously described. Abstract: Introduction and importance: There are limited reports in the literature of radical surgical resection for pancreatic neuroendocrine carcinoma (PNEC). In patients with non-functioning PNEC (NF-PNEC) within the tail of the pancreas tumours can cause splenic vein thrombosis (SVT) and subsequent sinitral portal hypertension (SPH). Radical surgical resection in such patients with concomitant liver metastasis has not previously been reported. Case presentation: We present a 67-year old female patient who presented with a large NF-PNEC within the tail of the pancreas with liver metastasis. We performed a distal pancreatectomy, splenectomy, partial gastrectomy and liver resection to achieve radical resecton. Discussion: All patients with NF-PNEC within the tail of the pancreatic should be considered for radical surgical resection. In the presence of multi-visceral involvement and complications such as SVT and/or SPH multi-speciality surgical expertise is likely to be required. Conclusion: Radical multi-visceral resection for large NF-PNEC can be safely performed in the presence of SVT and SPH.